The e-cigarette psychosocial environment, e-cigarette use, and susceptibility to cigarette smoking - Barrington-Trimis, Jessica L. (J Adolesc Health, 2016)
PURPOSE: One concern regarding the recent increase in adolescent e-cigarette use is the possibility that e-cigarettes may be used by those who might not otherwise have used cigarettes, and that dual use, or transition to cigarette use alone, may follow. METHODS: Questionnaire data were obtained in 2014 from 11(th)/12(th) grade students attending schools in 12 communities included in the Southern California Children’s Health Study (CHS). We evaluated the cross-sectional association between e-cigarette use, the psychosocial environment (family and friends’ use and approval of e-cigarettes and cigarettes) and susceptibility to future cigarette use among never cigarette smokers (N=1694), using previously validated measures based on reported absence of a definitive commitment not to smoke. RESULTS: Among adolescents who had never used cigarettes, 31.8% of past e-cigarette users and 34.6% of current (past 30 day) e-cigarette users indicated susceptibility to cigarette use, compared to 21.0% of never e-cigarette users. The odds of indicating susceptibility to cigarette use were two times higher for current e-cigarette users compared to never users (OR=1.97; 95%CI: 1.21, 3.22). A social environment favorable to e-cigarettes (friends’ use of and positive attitudes toward use of e-cigarettes) was also associated with greater likelihood of susceptibility to cigarette use, independent of an individual’s e-cigarette use. CONCLUSIONS: E-cigarette use in adolescence, and a pro-e-cigarette social environment, may put adolescents at risk for future use of cigarettes. E-cigarettes may contribute to subsequent cigarette use via nicotine addiction or social normalization of smoking behaviors.